Paleomagnetic observations at three locations in the Pleistocene lava sequence of southwest and south Iceland (Dataset) ... - Kristjánsson, Leó (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic observations at three locations in the Pleistocene lava sequence of southwest and south Iceland ...